Assessing Multimedia Quality from the User - Yahya, Yazrina; Donaldson, John; Jenkins, John (Malaysian Journal of Computer Science, 1999)
To assess multimedia quality from the user?s perspective, elicitation of information through the use of custom designed questionnaires is proposed. The paper discusses the type of information needed from users in order to accurately assess the quality, and provides reasons why that information is necessary. Quality perception is a relative concept which very much depends on the nature of the content, the individual making the assessment and the context in which any such judgement is made.